2021
DOI: 10.3389/fimmu.2021.789905
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Conserved Peptide Vaccine Candidate Activates Both Humoral and Cellular Immunity Against SARS-CoV-2 Variant Strains

Abstract: Facing the imminent need for vaccine candidates with cross-protection against globally circulating severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) mutants, we present a conserved antigenic peptide RBD9.1 with both T-cell and B-cell epitopes. RBD9.1 can be recognized by coronavirus disease 2019 (COVID-19) convalescent serum, particularly for those with high neutralizing potency. Immunization with RBD9.1 can successfully induce the production of the receptor-binding domain (RBD)-specific antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…In this study, mice immunized with oEV-S1 via mucosal routes (oral and IN) also exhibited an increased number of splenic plasma cells in comparison to mice treated with oEV vehicle alone. A similar result was also reported by Gao et al [ 61 ] as an increase in the ratio of CD19−CD138+ plasma cells in total lymphocytes derived from the spleen of mice immunized with RBD9.1 peptide.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, mice immunized with oEV-S1 via mucosal routes (oral and IN) also exhibited an increased number of splenic plasma cells in comparison to mice treated with oEV vehicle alone. A similar result was also reported by Gao et al [ 61 ] as an increase in the ratio of CD19−CD138+ plasma cells in total lymphocytes derived from the spleen of mice immunized with RBD9.1 peptide.…”
Section: Discussionsupporting
confidence: 89%
“…Vaccination with the entire Spike protein possessing mutated RBD, however, would not efficiently induce mutated RBD-specific Abs, as most of these Spike protein-specific Abs would be unable to detect the few mutated amino acids of RBD [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The development of vaccines that generate Abs able to neutralize hACE2-mediated infection requires a consideration of the domain antigen of RBD and the defined epitope antigen [ 15 , 16 , 17 , 18 , 19 ]. Clinical trials have reported that several RBD-containing vaccines could induce nAbs and protect against SARS-CoV-2 infection with acceptable adverse events [ 10 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…58G6 and 55A8 were 2 NAbs identified from patients convalescing from COVID-19 in early 2019 ( 31 , 38 40 ). 55A8 could bind to the spike (S) proteins of WT SARS-CoV-2 and its mutational variants, including Delta and Omicron BA.1, BA.2, and BA.5, as tested by enzyme-linked immunosorbent assay (ELISA) ( Supplemental Figure 1 , A and B; supplemental material available online with this article; https://doi.org/10.1172/jci.insight.171034DS1 ).…”
Section: Resultsmentioning
confidence: 99%